2014
DOI: 10.1111/gcb.12778
|View full text |Cite
|
Sign up to set email alerts
|

Changes in autumn vegetation dormancy onset date and the climate controls across temperate ecosystems in China from 1982 to 2010

Abstract: Vegetation phenology is a sensitive indicator of the dynamic response of terrestrial ecosystems to climate change. In this study, the spatiotemporal pattern of vegetation dormancy onset date (DOD) and its climate controls over temperate China were examined by analysing the satellite-derived normalized difference vegetation index and concurrent climate data from 1982 to 2010. Results show that preseason (May through October) air temperature is the primary climatic control of the DOD spatial pattern across tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
129
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 48 publications
(118 reference statements)
33
129
8
1
Order By: Relevance
“…The CCA patterns of EOS and temperature revealed that colder autumn temperatures were linked to earlier EOS in most areas of temperate China. In other words, higher temperature would lead to later EOS, which was consistent with other studies [12,19,65]. In comparison to temperature, preseason precipitation accounted for a smaller proportion of variance in EOS patterns.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The CCA patterns of EOS and temperature revealed that colder autumn temperatures were linked to earlier EOS in most areas of temperate China. In other words, higher temperature would lead to later EOS, which was consistent with other studies [12,19,65]. In comparison to temperature, preseason precipitation accounted for a smaller proportion of variance in EOS patterns.…”
Section: Discussionsupporting
confidence: 91%
“…One earlier study indicated that the onset date of dormancy of China's temperate vegetation was delayed in autumn by 3.7 days per decade from 1982 to 1999 [37]. Another study found that the autumn vegetation dormancy onset date over China's temperate ecosystems was delayed by 0.13 days per year from 1982 to 2010 [19]. Therefore, the magnitudes of trends found in previous studies were stronger than our estimate (0.7 days per decade).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Of these areas, 61.72% positively correlated with temperature and 79.31% positively correlated with precipitation. Yang et al (2014) suggested that the effect of temperature on plant growth will increase if the soil moisture constraints are released, especially in the semiarid areas. This demonstrates that maintaining the appropriate temperature and rainfall in autumn or winter can enhance the photosynthesis of vegetation, extending the growth process (Ciais et al 2005;Griffin et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for such enhancement of carbon sequestration was found to be the prolonged growing season . But now, more studies have focused on the shift in autumn phenology (Yang et al 2015). Wu et al (2013) found that a significant amount of the interannual variability in the annual net ecosystem productivity can be explained by the changes in the autumn phenology.…”
Section: Discussionmentioning
confidence: 99%